2013
DOI: 10.1007/s11062-013-9376-3
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Cognitive Impairment with No Dementia: Neuropsychology, Brain Imaging, and Event-Related Potentials

Abstract: We investigated the neuropsychological characteristics, cranial MRI, and P300 ERPs in patients suffering from vascular cognitive impairment with no dementia (VCIND). A study was performed on 68 cases of VCIND after stroke. The cranial MRI patterns and P300 waves of the patients were compared with those of 56 stroke patients without cognitive impairment and 52 healthy subjects. The MoCA (Montreal Cognitive Assessment) was also used to assess their mental status. The proportion of patients with frontotemporal le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
1
0
1
Order By: Relevance
“…In favor of some specificity of the above oddball ERP components, Podemski et al (2008) showed that mild VCI patients with leukoaraiosis and cortical atrophy had longer N2 and P3b peak latencies in relation to cognitive deficits compared with MCI patients with cortical atrophy only. Similarly, Jiang et al (2014Jiang et al ( , 2013 showed significantly longer auditory P3b peak latency in mild VCI patients in relation to frontotemporal lesions and leukoaraiosis, as compared with age-matched CU persons and patients who had suffered from stroke but without any cognitive impairment. This prolonged P3b latency was even higher for mild VCI patients with hyper-homocysteinemia ( Jiang et al, 2014 ).…”
Section: Oddball Event-related Eeg Potentials (Erps) Analyzed In the ...mentioning
confidence: 77%
“…In favor of some specificity of the above oddball ERP components, Podemski et al (2008) showed that mild VCI patients with leukoaraiosis and cortical atrophy had longer N2 and P3b peak latencies in relation to cognitive deficits compared with MCI patients with cortical atrophy only. Similarly, Jiang et al (2014Jiang et al ( , 2013 showed significantly longer auditory P3b peak latency in mild VCI patients in relation to frontotemporal lesions and leukoaraiosis, as compared with age-matched CU persons and patients who had suffered from stroke but without any cognitive impairment. This prolonged P3b latency was even higher for mild VCI patients with hyper-homocysteinemia ( Jiang et al, 2014 ).…”
Section: Oddball Event-related Eeg Potentials (Erps) Analyzed In the ...mentioning
confidence: 77%
“…Gangguan fungsi kognitif pada pasien stroke dapat didiagnosis lebih dini dengan menggabungkan tes neurologis dan tes P300 sehingga dapat memfasilitasi intervensi sewaktu-waktu dan memperbaiki prognosis. 12 Penelitian ini bertujuan untuk mengetahui hubungan nilai P300 dengan gangguan kognitif vaskular pada pasien stroke iskemik.…”
unclassified